Ceftiofur-Loaded Phbv Microparticles: A Potential Formulation for a Long-Acting Antibiotic to Treat Animal Infections - Constandil-Cordova, L; Vilos-Ortiz, C (2012)
The infectious diseases in the livestock breeding industry represent a significant drawback that generates substantial economic loss and have led to the indiscriminate use of antibiotics. The formulation of polymeric microparticles loaded with antibiotics for veterinary use can: reduce the number of required doses; protect the drug from inactivation; and maintain a sustained-release of the antibiotic drug at effective levels. Accomplishing all of these goals would have a significant economic and animal health impact on the livestock breeding industry. Results: In this work, we formulated ceftiofur-loaded PHBV microparticles (PHBV-CEF) with a spherical shape, a smooth surface and diameter sizes between 1.65 and 2.37 ?m. The encapsulation efficiency was 39.5 ± 1.1% w/w, and we obtained a sustained release of ceftiofur in PBS-buffer (pH 7.4) over 7 days. The antibacterial activity of ceftiofur was preserved after the encapsulation procedure, and toxicity of PHBV-CEF microparticles evaluated by MTS was represented by an IC50 > 10 mg/mL. Conclusions: Our results suggest that PHBV-CEF particles have a potential application for improving the treatment of infectious diseases in the livestock breeding industry. © 2012 by Pontificia Universidad Católica de Valparaíso, Chile.